Looking for (i)LUC - Laborde Debucquet, David (2013)
"Partnering for Impact: IFPRI-European Research Collaboration for Improved Food and Nutrition Security" presentation by David Laborde, IFPRI, 25 November 2013 in Brussels, Belgium.